Clinical recurrences of COVID-19 symptoms after recovery: Viral relapse, reinfection or inflammatory rebound?. Issue 5 (November 2020) - Gousseff, Marie; Penot, Pauline; Gallay, Laure; Batisse, Dominique; Benech, Nicolas; Bouiller, Kevin; Collarino, Rocco; Conrad, Anne; Slama, Dorsaf; Joseph, Cédric; Lemaignen, Adrien; Lescure, François-Xavier; et al.
Summary: For the first 3 months of COVID-19 pandemic, COVID-19 was expected to be an immunizing non-relapsing disease. We report a national case series of 11 virologically-confirmed COVID-19 patients having experienced a second clinically- and virologically-confirmed acute COVID-19 episode. According to the clinical history, we discuss either re-infection or reactivation hypothesis. Larger studies including further virological, immunological and epidemiologic data are needed to understand the mechanisms of these recurrences.